Three essays on urban economics: evidences from Brazil - CARAZZA, Luís Eduardo Barbosa (2016)
The present study examines the impact of three public policies in Brazil. The first essay examines the juvenile curfew in the interior of São Paulo and our estimates shows that this policy was responsible for the reduction of approximately 17.5% in the theft rate when compared to cities that did not adopt the curfew. The second article estimates the effect of the Dona Lindu Park in the price of real estate in the city of Recife, Pernambuco. The results indicate an increase in the value of approximately 7.7% of properties located up to 600 meters from the park and for properties located at 600 and 1000 meters from the park there is was negative impact on the real estate price of approximately 11.9%. In the third essay we studied the impact of the expansion of the Federal Network of Professional and Technological Education on Human Capital and migration variables and, according to our analysis; there was a positive impact of 2.59% on the proportion of short-term immigrants.